Kristy and the walking disaster - Martin, Ann M., 1955-; Crenshaw, Ellen T. (Baby-sitters Club (Graphix (Firm)), 2024)
"They're lean, they're mean, they're the pride of Stoneybrook. Who are they? They're Kristy's Krushers! When Kristy sees how much her little brothers and sister want to play on a softball team, she starts a ragtag team of her own. Maybe Kristy's Krushers aren't world champions (how could they be, with Jackie Rodowsky, walking disaster, playing for them?), but nobody beats them when it comes to team spirit. Now Bart's Bashers have challenged the Krushers to a game. It's bad enough that the Bashers truly are lean and mean--but what's worse is that Kristy has a crush on the Bashers' coach!"--